Neuroendocrine Whiplash: Slamming the Breaks on Anabolic-Androgenic Steroids Following Repetitive Mild Traumatic Brain Injury in Rats May Worsen Outcomes - Tabor, Jason; Collins, Reid; Debert, Chantel T.; Shultz, Sandy R.; Mychasiuk, Richelle (Frontiers in Neurology, 2019)
Sport-related concussion is an increasingly common injury among adolescents, with repetitive mild traumatic brain injuries (RmTBI) being a significant risk factor for long-term neurobiological and psychological consequences. It is not uncommon for younger professional athletes to consume anabolic-androgenic steroids (AAS) in an attempt to enhance their performance, subjecting their hormonally sensitive brains to potential impairment during neurodevelopment. Furthermore, RmTBI produces acute neuroendocrine dysfunction, specifically in the anterior pituitary, disrupting the hypothalamic-pituitary adrenal axis, lowering cortisol secretion that is needed to appropriately respond to injury. Some AAS users exhibit worse symptoms post-RmTBI if they quit their steroid regime. We sought to examine the pathophysiological outcomes associated with the abrupt cessation of the commonly abused AAS, Metandienone (Met) on RmTBI outcomes in rats. Prior to injury, adolescent male rats received either Met or placebo, and exercise. Rats were then administered RmTBIs or sham injuries, followed by steroid and exercise cessation (SEC) or continued treatment. A behavioural battery was conducted to measure outcomes consistent with clinical representations of post-concussion syndrome and chronic AAS exposure, followed by analysis of serum hormone levels, and qRT-PCR for mRNA expression and telomere length. RmTBI increased loss of consciousness and anxiety-like behavior, while also impairing balance and short-term working memory. SEC induced hyperactivity while Met treatment alone increased depressive-like behavior. There were cumulative effects whereby RmTBI and SEC exacerbated anxiety and short-term memory outcomes. mRNA expression in the prefrontal cortex, amygdala, hippocampus, and pituitary were modified in response to Met and SEC. Analysis of telomere length revealed the negative impact of SEC while Met and SEC produced changes in serum levels of testosterone and corticosterone. We identified robust changes in mRNA to serotonergic circuitry, neuroinflammation, and an enhanced stress response. Interestingly, Met treatment promoted glucocorticoid secretion after injury, suggesting that maintained AAS may be more beneficial than abstaining after mTBI.